Polycystic Ovarian Syndrome Treated by Homoeopathy: An Evidence-Based Case Report - Nahar, Laijun; Shil, Ratan Chandra (Homœopathic Links, 2024)
Background Polycystic ovarian syndrome (PCOS) is one of the most common endocrinopathies among reproductive women. Cardinal manifestations of PCOS include hyperandrogenism, oligo/anovulation and/or polycystic ovarian morphology. Affected women often display notable metabolic co-morbidities. Plenty of evidence on PCOS favouring homoeopathy is available in the literature. In this case, also individualised medicine portrayed a favourable response within a short span of time.Case Summary A case of PCOS with the complaint of irregular, delayed menses, acne on the face and dark pigmentation on the neck for the last 3 years is presented here. The outcome was assessed by using two validated measurement scales. After 4 months of follow-up, the case was markedly improved on the Outcome Related to Impact on Daily Living (ORIDL) scale (+4) as per the patient's perspective. Clinical improvement was correlated with objective evidence from the ultrasonography report. Modified Naranjo criteria for Homeopathy (MONARCH) score recorded at the final visit (+8 on the ‘−6 to 13’ scale) is suggestive of a high likelihood of improvement by homoeopathic intervention.Conclusion The case report presented here has produced significant evidence of the effect of individualised homoeopathic medicine in the treatment of PCOS within a short time.
Keywords: polycystic ovarian syndrome; individualised homoeopathic; MONARCH; case report